High Accuracy Generation and Test of B0 Signals on Magnetic Resonance Imaging Spectrometer - CUI Yan; XIAO Liang (Chinese Journal of Magnetic Resonance, 2018)
A field programmable gate array (FPGA)-based method is proposed to generate B0 signals, with high accuracy, on magnetic resonance imaging (MRI) spectrometers. The FPGA reads the waveform data and external parameters, and stores them in the dual-port random access memory (RAM) and parameter registers, respectively. The B0 signals are then generated using the pre-emphasis algorithm, and different time or amplitude parameters give different B0 signals. The B0 signals are collected by high speed acquisition card, and the least squares fitting algorithm is used to test the accuracy of the B0 signals generated. The performance of this method was validated by experiments.